Arterial Embolization and Methylene Blue Injection into the Aberrant Artery in Two Infants with Intralobar Sequestration - Accarain, Anna Ayako; Laureys, Marc; Joyeux, Luc; Damry, Nasroola; Steyaert, Henri; Reusens, Helena (European Journal of Pediatric Surgery Reports, 2022)
Bronchopulmonary sequestration is a rare congenital lung dysplasia. An intralobar sequestration (ILS) is a nonfunctional mass within the lung parenchyma without bronchial communication and with aberrant systemic arterial blood supply. Surgical resection or close observation can be proposed in the management of asymptomatic and low-risk ILS, but there is a lack of consensus. Endovascular embolization before thoracoscopic resection of ILS has been described to limit perioperative bleeding. Another technique previously reported is the injection of methylene blue in the feeding artery to macroscopically mark the sequestration from the healthy lung. In that way, a nonanatomical resection can be performed instead of a lobectomy without the risk of leaving abnormal lung tissue in place. We describe the first two cases of these two techniques combined: a 3-year-old girl with an ILS in the right lower lobe with an artery originating from the abdominal aorta, and a 14-month-old girl with an ILS in the right lower lobe with an artery coming from the celiac trunk.The combination of embolization and injection of methylene blue in the aberrant artery leads to a clear macroscopic demarcation of the blue-colored ILS from the healthy lung parenchyma and allowed safe nonanatomical resection of the ILS without risk of bleeding or compromising normal lung tissue.
Keywords: VATS; hybrid management; intralobar sequestration